2009
DOI: 10.3174/ajnr.a1498
|View full text |Cite
|
Sign up to set email alerts
|

Relative Decrease in Signal Intensity of Subcortical White Matter in Spontaneous Intracranial Hypotension on Fluid-Attenuated Inversion Recovery Images

Abstract: BACKGROUND AND PURPOSE:In reviewing MR images of patients with spontaneous intracranial hypotension (SIH), we found an accentuated decrease in the subcortical white matter on fluidattenuated inversion recovery (FLAIR) images. Our aim was to determine whether the signal intensity of the subcortical white matter decreases on FLAIR and T2-weighted images in SIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Once considered a rare entity, recent understanding of the pathophysiology and the radiologic identification of this syndrome resulted in the increase in the number of recognized cases, and recent reports showed that the incidence of this syndrome may be indeed much higher than presumed [1,5,9,14]. The estimated incidence of SIH is 1:50,000, with a female predominance [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once considered a rare entity, recent understanding of the pathophysiology and the radiologic identification of this syndrome resulted in the increase in the number of recognized cases, and recent reports showed that the incidence of this syndrome may be indeed much higher than presumed [1,5,9,14]. The estimated incidence of SIH is 1:50,000, with a female predominance [6].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous intracranial hypotension (SIH) is a clinical syndrome in which absolute or relative hypovolemia of the cerebrospinal fluid (CSF) results in various neurological symptom [1]. SIH is nearly always characterized by orthostatic headache [18].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, an increased amount of deoxyhemoglobin related to venous stasis has been advocated to explain subcortical low-intensity images on long TR in spontaneous intracranial hypotension. 5 Venous stasis resulting in an increased amount of dehoxyhemoglobin may be advocated also in leptomeningeal diseases. Additional MR parameters resulting from magnetization transfer ratios, T2 relaxation times, metabolite concentrations by in vivo proton spectroscopy, and the more recently developed susceptibilityweighted imaging technique 6,7 should provide new understanding of the disease processes.…”
Section: Discussionmentioning
confidence: 99%